(untitled) (Comprehensive Journal of Science, 2025)
This study evaluated the effects of Moringa leaves and ginger powder supplementation on the productive performance and serum biochemical parameters of Japanese quail. A total of 270 seven-day-old quails were used in a five-week trial. The birds were assigned to three dietary treatments: T1 (control, no additives), T2 (0.4% Moringa leaves), and T3 (0.2% ginger powder). Body weight and feed consumption were recorded weekly until day 42, and the feed conversion ratio (FCR) was calculated. Blood samples were collected at 42 days for biochemical analysis; the results demonstrated that the inclusion of Moringa leaves and ginger powder significantly improved (P≤0.05) body weight, weight gain, and FCR. Serum analysis revealed increased albumin and globulin levels alongside reduced glucose concentrations. Additionally, supplementation led to a significant decrease in triglycerides and plasma cholesterol levels compared to the control group. High-density lipoprotein (HDL) and total antioxidant capacity (TAC) were elevated, whereas low-density lipoprotein (LDL), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels were reduced in conclusion, the dietary inclusion of Moringa leaves and ginger powder enhanced feed efficiency, improved lipid metabolism, and boosted antioxidant capacity in Japanese quail. These findings suggest that both additives can serve as natural growth enhancers while promoting better health parameters in poultry production.